2021
DOI: 10.1021/acsagscitech.1c00178
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of a Nanocellulose Superabsorbent and Its Effect on the Growth of Spinach (Spinacea oleracea)

Abstract: In this study, spinach (Spinacea oleracea) plants were grown in two soils, a clay loam (CL) and a sandy (SD) soil, amended with two types of superabsorbent polymers (SAPs), nanocellulose and commercial, at different levels of soil moisture: 70, 40, and 20%. The effect of the superabsorbent on the soil properties, water management, and plant biomass was measured and compared to that in soils treated with a commercial anionic polyacrylamide-based SAP. Plant biomass is the highest in SD soil amended with a commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 53 publications
(96 reference statements)
0
14
0
1
Order By: Relevance
“…It is known that SAPs based on natural polymers are superior to those based on synthetic polymers in biodegradability but inferior in water uptake and soil amendment efficiency [ 23 ]. These basic features of SAPs based on nanocellulose were confirmed in [ 76 ], where nanoscale cellulose-based superabsorbents were prepared using the (2,2,6,6-tetramethylpiperidin-1-yl)oxyl (TEMPO)-mediated oxidation method [ 77 , 78 ] from Bleached Eucalyptus Kraft (BEK) pulp (Australian Paper, Maryvale, QLD, Australia) with a chemical composition of cellulose (78.8% ± 0.8), hemicellulose (17.7% ± 0.4), lignin (3.2% ± 0.1), extractives (0.3% ± 0.1), and ash (0.2% ± 0.1) [ 79 ]. The properties of the prepared nanocellulose-based SAP were compared to those of a commercial anionic PAM-based SAP.…”
Section: Superabsorbent Polymer Hydrogelsmentioning
confidence: 59%
See 1 more Smart Citation
“…It is known that SAPs based on natural polymers are superior to those based on synthetic polymers in biodegradability but inferior in water uptake and soil amendment efficiency [ 23 ]. These basic features of SAPs based on nanocellulose were confirmed in [ 76 ], where nanoscale cellulose-based superabsorbents were prepared using the (2,2,6,6-tetramethylpiperidin-1-yl)oxyl (TEMPO)-mediated oxidation method [ 77 , 78 ] from Bleached Eucalyptus Kraft (BEK) pulp (Australian Paper, Maryvale, QLD, Australia) with a chemical composition of cellulose (78.8% ± 0.8), hemicellulose (17.7% ± 0.4), lignin (3.2% ± 0.1), extractives (0.3% ± 0.1), and ash (0.2% ± 0.1) [ 79 ]. The properties of the prepared nanocellulose-based SAP were compared to those of a commercial anionic PAM-based SAP.…”
Section: Superabsorbent Polymer Hydrogelsmentioning
confidence: 59%
“…The properties of the prepared nanocellulose-based SAP were compared to those of a commercial anionic PAM-based SAP. It was shown for clay loam (CL) and sandy (SD) soil that both commercial and nanocellulose SAPs improved the water retention ( Figure 20 a), decreased soil density ( Figure 20 b) and increased soil porosity ( Figure 20 c), but all these effects are more pronounced for the synthetic SAP than for the cellulose-based one [ 76 ].…”
Section: Superabsorbent Polymer Hydrogelsmentioning
confidence: 99%
“…As the world progresses towards a renewable future, cellulose is becoming increasingly popular as a platform molecule for superabsorbent materials due to its low-cost, biocompatibility, and ability to modify for desired applications ( Alam et al, 2019 ; Mendoza et al, 2019a ; Barajas-Ledesma et al, 2020 ; Zainal et al, 2021 ). In our previous work we have investigated the synthesis and properties of TEMPO-oxidized cellulose-based hydrogels for agricultural and biomedical applications ( Mendoza et al, 2019b ; Curvello et al, 2019 ; Barajas-Ledesma et al, 2020 ; Hossain et al, 2021 ; Barajas-Ledesma et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…24−30 The fiber structure has also been explored for water retention and controlled release of fertilizers, such as nitrogen (N), phosphorus (P), and potassium (K), for better development of seeds and seedlings, thus generating plants with greater stem height and number and size of leaves. 31,32 From micro-to nanoscale fibrillar structure, it is possible to control nutrient release and water retention. 33,34 In addition to the fibrillar structure, the possibility of cellulose regeneration enhances the application of natural fibers in the controlled release of nutrients, as reported in the literature.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The fiber structure has also been explored for water retention and controlled release of fertilizers, such as nitrogen (N), phosphorus (P), and potassium (K), for better development of seeds and seedlings, thus generating plants with greater stem height and number and size of leaves. , From micro- to nanoscale fibrillar structure, it is possible to control nutrient release and water retention. , In addition to the fibrillar structure, the possibility of cellulose regeneration enhances the application of natural fibers in the controlled release of nutrients, as reported in the literature . In this way, the fibers are used to compose materials for agricultural applications such as mulch, , mats, superabsorbents, , composites, and papers. , These studies have demonstrated the efficiency of fibers in promoting the proper release of nutrients for plant growth against the backdrop of high demand of fertilizers for global food production. , …”
Section: Introductionmentioning
confidence: 99%